Theoretical study of plasmon resonances in linear chain of silver nanowires - Stognii, N. P.; Sakhnenko, N. K. (IEEE, 2011)
In this paper we investigate the plasmon resonance coupling in linear chain of infinite silver nanowires. It was shown the dependence of the resonant peaks location and their magnitudes on the illumination direction and on the distance between the nanowires. The Mie series expansion is used to derive the solution.
Keywords: plasmon resonance; nanowires